Interindividual Variability Response to Resistance and High-Intensity Interval Training on Blood Pressure Reduction in Hypertensive Older Adults - Johnattan Cano-Montoya; Nicolas Hurtado; Carolina Núñez Vergara; Sebastián Báez Vargas; Marcela Rojas-Vargas; Sergio Martínez-Huenchullán; Cristian Alvarez; Mikel Izquierdo (Journal of Cardiovascular Development and Disease)
Background: This study evaluated the effects of resistance training (RT) and high-intensity interval training (HIIT) on systolic (SBP) and diastolic blood pressure (DBP) in hypertensive older adults undergoing pharmacological therapy over four and eight weeks. We compared the efficacy of RT and HIIT in reducing non-responders (NRs) between weeks 4 and 8 and analyzed time-course adaptations in NRs and responders (Rs). Methods: Thirty-nine participants were randomized into RT-G (n = 13), HIIT-G (n = 13), or control (CG, n = 13) groups. RT utilized elastic bands, and HIIT involved cycle ergometers, with three weekly 30 min sessions for 8 weeks. SBP and DBP were measured before intervention and at weeks 4 and 8, respectively. Individual responses were classified as NRs or Rs using the Hopkins method (SDIR = √[SDExp2–SDCon2]). Time-course adaptations were evaluated. Results: Both the RT-G and HIIT-G reduced SBP at 8 weeks (RT-G: −13 mmHg; [ES: 1.12]; HIIT-G: −12 mmHg [ES: 0.8]; both p < 0.05). The proportion of NRs for SBP decreased from 46% to 38% in RT-G and 69% to 46% in HIIT-G. Rs showed a peak SBP reduction at 4 weeks (−14.7 and −25.5 mmHg), stabilizing by week 8 (−22.8 and −19.6 mmHg) in RT-G and HIIT-G, respectively. Conclusion: Eight weeks of RT and HIIT effectively reduced SBP and NR prevalence, with time-course adaptations favoring Rs.